A Dynamically Stabilized Single‐Nickel Electrocatalyst for Selective Reduction of Oxygen to Hydrogen Peroxide. Issue 64 (9th November 2018) - Wang, Tingting; Zeng, Zhongming; Cao, Lingyun; Li, Zhe; Hu, Xuefu; An, Bing; Wang, Cheng; Lin, Wenbin
Abstract: On‐location electrochemical generation of H2 O2 is of great current interest. Herein, selective two‐electron reduction of O2 to H2 O2 by a single [Ni II (H2 O)6 ] 2+ cation that is dynamically associated with a negatively charged metal–organic layer (MOL) by hydrogen bonding and coulombic interactions is reported. In contrast, Ni II centers covalently immobilized on the MOL reduce O2 to H2 O in a four‐ electron process. Oxygen adsorption by [Ni II (H2 O)6 ] 2+ followed by two‐electron reduction generates neutral [Ni II (H2 O)4 (OH)(OOH)] 0, which momentarily disconnects from the negatively charged MOL to avoid the injection of additional electrons. Release of H2 O2 from [Ni II (H2 O)4 (OH)(OOH)] 0 regenerates [Ni II (H2 O)6 ] 2+, which regains affinity to the MOL. Such dynamically associated Ni II single‐metal electrocatalysts ensure high selectivity and represent a new strategy for generating selective catalysts for electrochemical production of important chemicals. Abstract : Dynamic duo : An Ni aqua complex weakly associated with a metal–organic layer (MOL)‐modified electrode is an efficient catalyst for O2 reduction to H2 O2 (see scheme). Momentary stabilization of the mobile Ni complex by dynamic secondary interactions with the MOL avoids formation of nanoparticles, and Ni II species can undergo efficient electron transfer and detach from the electrode to avoid over‐reduction of H2 O2 . In contrast, Ni centers immobilized by Hf‐O‐Ni linkage to the MOL selectively give H2 O as the product.